2009
DOI: 10.1088/0004-637x/700/2/1658
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Long-Period Oscillations in Euv Filaments Near to Eruption: Two-Wavelength Correlation and Seismology

Abstract: We investigate whether or not ultra-long-period oscillations in EUV filaments can be related to their eruption. We report new observations of long-period (∼10-30 hr) oscillatory motions in an apparently quiescent filament, as it crosses the solar disk in a 12 minute cadence SOHO/Extreme-Ultraviolet Imaging Telescope (EIT) 195 Å uninterrupted data set. This data set is chosen to explore characteristics of the filament oscillations depending on its eruptive behavior, which is observed while the filament is still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 37 publications
3
27
0
Order By: Relevance
“…Wang et al (2009) reported two significant periodicities of 12 and 25 min in the intensity and Doppler shift variations over a coronal diffuse structure with Hinode/EIS. Prominence oscillations with periods ranging from 20 min up to several hours were reported as well (Foullon et al 2004(Foullon et al , 2009Tripathi et al 2009;Hershaw et al 2011).…”
Section: Introductionmentioning
confidence: 91%
“…Wang et al (2009) reported two significant periodicities of 12 and 25 min in the intensity and Doppler shift variations over a coronal diffuse structure with Hinode/EIS. Prominence oscillations with periods ranging from 20 min up to several hours were reported as well (Foullon et al 2004(Foullon et al , 2009Tripathi et al 2009;Hershaw et al 2011).…”
Section: Introductionmentioning
confidence: 91%
“…The dominant period is 12.1 h. Pouget et al (2006) report five to six hour period oscillations detected in the Doppler velocity of a quiescent filament, in He I at 584.33 Å. Foullon et al (2009) show that the long period detected in a quiescent filament, using 195 Å images, increases prior to its eruption.…”
Section: Introductionmentioning
confidence: 94%
“…However, this classification (solely based on the period value) is far from complete: Balthasar et al (1993) observed a prominence simultaneously with the GCT and VTT telescopes in Tenerife to remove doubts about the instrumental or atmospheric origin of prominence oscillations and obtained strong power in the Doppler shift from both telescopes with period around 30 s; hence, very short-period small amplitude oscillations also exist. Furthermore, a few works in which prominences have been observed from space during extended time intervals show that very long-period oscillations also exist: Pouget et al (2006) detected periodicities of 5 -6 h, while Foullon et al (2004) and Foullon et al (2009) have observed variations in EUV filaments with periods around 12 h, and 10 -30 h, respectively. Although the classification in terms of shortperiod, long-period, etc.…”
Section: Detected Periodsmentioning
confidence: 99%